Recent insight into the prevalence, etiology, and outcome of epistaxis in a university hospital in Saudi Arabia - Sami E Alharethy (Wolters Kluwer Medknow Publications, 2019)
Objectives: The objective of the study is to study the prevalence, pattern, etiology, and outcome of epistaxis in a tertiary university hospital. Methods: A retrospective study conducted at King Abdulaziz University Hospital, King Saud University, Riyadh, Saudi Arabia, from January 2014 to January 2017. Patients' demographics, causes of bleeding, and management techniques were recorded. This study was approved by the Institutional Review Board at King Saud University. Results: A total of 1126 patients had an epistaxis prevalence rate of 0.98% of all emergency visits. There were 462 males (41.0%) and 664 females (59.0%). The mean age was 39.1 years (from 6 to 74 years). The highest number of patients with epistaxis was 340 (30.2%) in age group of 41-50 years. The mean height was 144.6 cm and the mean weight was 56 kg. The most common cause of epistaxis was idiopathic in 353 (31.3%) patients. A total of 510 (45.3%) patients had an anterior bleeding site, while 152 (13.5%) had bilateral bleeding. The diagnosis was reached both endoscopic and clinical. The majority were treated with a nonsurgical method; anterior packing was successful in 840 (74.6%) patients and chemical and electric cautery in 80 (7.1%) patients. There was a history of recurrent epistaxis in 46 children (4.1%). No mortality occurred during the study period. Conclusion: Epistaxis is common in Saudi Arabia. The age group of 41-50 years is more prone to epistaxis with a prevalence of 30.2%. Exposure to dry, hot weather, idiopathic, and hypertension are the frequent causes. Packing and cauterization successfully treated epistaxis in most cases, and there were no cases with mortality.